986 LEFT VENTRICULAR LEAD PLACEMENT FOR BIVENTRICULAR PACING INTO A LEFT LATERAL VEIN IN PATIENT WITH CONGENITAL ATRESIA OF THE CORONARY SINUS OSTIUM WHO UNDERWENT AORTIC VALVE REPLACEMENT. (15th December 2022) - Santoro, Amato; Barilli, Maria; Marallo, Carmine; Cameli, Matteo
Abstract: Introduction: Coronary sinus ostial atresia (CSOA) is a rare congenital heart anomaly consisting in the occlusion of the coronary sinus (CS) outlet in the right atrium. It is one of the causes of placement left lead failure in CS during cardiac resynchronization therapy (CRT) device implantation. The persistence of the left superior vena cava is the most common pathway that allows venous blood flow to drain into the right atrium and can represent a new possible way to reach a left ventricular vein from the CS. Methods: A 66-year-old male suffering from sarcoidosis was studied after an episode of syncope under exertion. EKG showed a 1st degree atrioventricular block and a left bundle branch block (LBBB) with wide QRS (170 ms). Echocardiography found left ventricle dilatation, severe systolic dysfunction, and a severe low-flow low-gradient aortic stenosis for which he underwent aortic valve replacement. After surgery and finding of 2nd degree type II atrioventricular block, CRT implant was performed but the procedure was complicated by the finding of CSOA. The insertion of the left quadripolar lead along a left branch of the occluded CS was achieved with a push-and-pull technique of the lead over a guidewire, after the retrieval and the cannulation of the persistent left superior vena cava. Results: A new approach was applied on a rare case of CSOA found during CRT procedure. The contrast medium (CM) in the left subclavian vein revealed the existence of the left superior vena cava that was than cannulated. CM injection in CS highlighted a posterior left branch that was approached with a specific guidewire and a subselector after selective venography. With a fine technique of sliding of the lead on a tensioned guidewire, the quadripolar catheter was successfully placed in the left ventricular vein. Left-ventricle-right ventricle delays and catheter thresholds were tested and a final QSR duration of 90 msec in CRT mode was obtained. Conclusions: This case-report shows a complex technique, reported in parallel with other similar procedures, to help the approach toward a rare anatomical variant of CSOA accompanied by persistent left superior vena cava when a CRT implant is needed after cardiac valve surgery in a patient suffering from sarcoidosis.